On Some Properties of Ap Weights - Nath, Jayadev (Api Journal of Science, 2024)
We provide a survey of the literature on the issue of weighted inequalities of operators in harmonic analysis. Some features of Ap weight functions are discussed and elaborated in this note that will assist in the comprehensive study on the theory of weights.